Benach, Núria i Albet, Abel (2010): Edward W. Soja: La perspectiva postmoderna de un geógrafo radical - Estévez Villarino, Brais (Documents d’Anàlisi Geogràfica, 2011)
Benach, Núria i Albet, Abel (2010) Edward W. Soja: La perspectiva postmoderna de un geógrafo radical Barcelona: Icaria, 285 p. ISBN: 978-84-9888-243-8